Pengaruh Net Profit Margin(Npm), Cash Ratio(Car), Dan Price To Book Value (PBV) Terhadap Harga Saham Pada Perusahaan Sub Sektor Konstruksi Dan Bangunan Yang Terdaftar Di Bursa Efek (BEI) Periode 2017-2021 - Wiwid Putri Altin; Kardinal Kardinal (LPPM Universitas Multi Data Palembang, 2023)
This study aims (1) to partially observe the effect of NPM, CAR, and PBV on share prices in Constructionand Building Sub-Sector companies Listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. (2) tosee the effect of NPM, CAR, and PBV simultaneously on stock prices. The population of this research is 14 companiesusing purposive sampling method. Data analysis techniques using the Classical Assumption Test, Multiple LinearRegression, and Hypothesis testing, the data is processed using the SPSS version 23 application. Partial researchresults show that Net Profit Margin (X1) has a significant effect on stock prices, Cash ratio (X2) has a significanteffect on stock prices, and Price to Book Value (X3) has a significant effect on stock prices. The results of the studysimultaneously show that Net Profit Margin (X1), Cash Ratio (X3), and Price To Book Value(X4) have a positive effect on stock prices.